2011
DOI: 10.1158/1078-0432.ccr-11-0793
|View full text |Cite
|
Sign up to set email alerts
|

Phase I Dose-Finding Study of Pazopanib in Hepatocellular Carcinoma: Evaluation of Early Efficacy, Pharmacokinetics, and Pharmacodynamics

Abstract: Background: A phase I dose-escalating study of pazopanib was conducted to determine the maximum tolerated dose (MTD), pharmacokinetic/pharmacodynamic relationships, and clinical activity in patients with advanced hepatocellular carcinoma (HCC).Experimental Design: Asian patients (N ¼ 28) were dose escalated on pazopanib (200-800 mg) once daily (QD) on 21-day cycles, with MTD as the primary endpoint using a modified 3 þ 3 design. Changes in tumor vasculature were evaluated by dynamic contrast-enhanced MRI (DCE-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 80 publications
(49 citation statements)
references
References 28 publications
3
45
1
Order By: Relevance
“…The efficacy end points of this combination, including a response rate of 6%, a PFS-16W of 35.3% and a median PFS of 2.7 months in a cohort of patients enrolled from Asian countries where hepatitis B virus infection is endemic, were comparable to those of sorafenib and other previously reported antiangiogenic therapies [4,9,10,27]. However, the efficacy of the combination demonstrated in this Asian cohort did not meet the preplanned efficacy boundary of 60% PFS-16W, nor was it as effective as initially reported by Thomas et al [17 ]in a USA-based patient cohort.…”
Section: Discussionsupporting
confidence: 57%
“…The efficacy end points of this combination, including a response rate of 6%, a PFS-16W of 35.3% and a median PFS of 2.7 months in a cohort of patients enrolled from Asian countries where hepatitis B virus infection is endemic, were comparable to those of sorafenib and other previously reported antiangiogenic therapies [4,9,10,27]. However, the efficacy of the combination demonstrated in this Asian cohort did not meet the preplanned efficacy boundary of 60% PFS-16W, nor was it as effective as initially reported by Thomas et al [17 ]in a USA-based patient cohort.…”
Section: Discussionsupporting
confidence: 57%
“…Hsu et al [110] Thalidomide Perfusion CT 18 High baseline blood flow and blood volume correlates with progression Petralia et al [119] Thalidomide/ radiotherapy DCEMRI [120] CT …”
Section: Imaging Biomarkersmentioning
confidence: 99%
“…Data from clinical trials on a variety of molecular targeted therapies for advanced HCC are shown in table 1[3,4,5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56]. …”
Section: Clinical Trials Of Molecular Targeted Therapy For Advanced Hccmentioning
confidence: 99%